1996
DOI: 10.3171/jns.1996.85.1.0019
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of brain arteriovenous malformations by embolization and radiosurgery

Abstract: Embolization was used to reduce the size of brain arteriovenous malformations (AVMs) prior to radiosurgical treatment in 125 patients who were poor surgical candidates or had refused surgery. Of these patients, 81% had suffered hemorrhage, and 22.4% had undergone treatment at another institution. According to the Spetzler-Martin scale, the AVMs were Grade II in 9.6%, Grade III in 31.2%, Grade IV in 30.4%, and Grades V to VI in 28.8% of the cases. Most embolizations were performed using cyanoacrylate delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
146
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(154 citation statements)
references
References 40 publications
2
146
0
6
Order By: Relevance
“…47 Gobin et al have reported that preradiosurgical embolization reduced average AVM volumes by more than 30% in their cohort of 125 patients and allowed for a 65% rate of AVM cure in the patients rendered suitable for radiosurgery after embolization. 48 Obliteration rates of 60% to 81% have been reported by other groups. 41 It is noteworthy, however, that a number of reports indicate a negative association between successful AVM radiosurgical obliteration and previous embolization.…”
Section: Preradiosurgical Embolizationmentioning
confidence: 59%
See 1 more Smart Citation
“…47 Gobin et al have reported that preradiosurgical embolization reduced average AVM volumes by more than 30% in their cohort of 125 patients and allowed for a 65% rate of AVM cure in the patients rendered suitable for radiosurgery after embolization. 48 Obliteration rates of 60% to 81% have been reported by other groups. 41 It is noteworthy, however, that a number of reports indicate a negative association between successful AVM radiosurgical obliteration and previous embolization.…”
Section: Preradiosurgical Embolizationmentioning
confidence: 59%
“…Such patients typically have small AVMs with few feeding pedicles, noncompartmental fistulous (rather than plexiform) niduses, and no perinidal angiogenesis. 18,41,42,48,54 Additionally, use of Onyx has been associate with higher rates of AVM cure by embolization than previously seen with other embolic agents. 41 …”
Section: Curative Embolizationmentioning
confidence: 99%
“…Concerning obliteration rate, the multivariate analysis clearly shows that lesions with less than 2/3 obliteration had proportionally higher rebleeding rates. Gobin did not observe this association in partially embolized patients who later underwent radiosurgery, but this might be explained by the fact that in that study a multivariate technique was not used for data analysis 22 . Our patients with less than 1/3 obliteration bled even more often than expected had the lesion been untreated.…”
Section: A B Cmentioning
confidence: 80%
“…it is exactly in small lesions that embolization has the highest rates of cure 8,22 . Luessenhop 16 observed that partial embolization may reduce the risk of hemorrhage by reducing intranidal pressure.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation